2017
DOI: 10.1080/09540121.2017.1363369
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on biomedical HIV prevention options among women who inject drugs in Kenya

Abstract: Due to heightened vulnerability to HIV from frequent engagement in sex work and overlapping drug-using and sexual networks, women who inject drugs should be a high priority population for pre-exposure prophylaxis (PrEP) and other biomedical HIV prevention tools. Kenya is one of the first African countries to approve oral PrEP for HIV prevention among "key populations," including people who inject drugs and sex workers. The objective of this study was to explore preferences and perceived challenges to PrEP adop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Very few studies reported clear opposition to PrEP as an HIV prevention tool, although some generated evidence of community distrust of study/trial designs or of the concept of PrEP itself [21]. Theoretical studies among potential end-users typically found high acceptability of PrEP [22][23][24][25][26][27][28][29][30][31]. By including the theoretical research, a range of regimens are included in the review including: oral daily and intermittent (the definition of which is particular to the given study), as well as emerging injectable and vaginal ring products.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Very few studies reported clear opposition to PrEP as an HIV prevention tool, although some generated evidence of community distrust of study/trial designs or of the concept of PrEP itself [21]. Theoretical studies among potential end-users typically found high acceptability of PrEP [22][23][24][25][26][27][28][29][30][31]. By including the theoretical research, a range of regimens are included in the review including: oral daily and intermittent (the definition of which is particular to the given study), as well as emerging injectable and vaginal ring products.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies suggest that PrEP is conflated with ART not just in personal understandings of PrEP but in expectations of how others will respond, generating fear of HIV‐related stigma and discrimination. This potential stigma has been highlighted among MSM in Kenya ; women who inject drugs in Kenya ; female sex workers in Kenya and South Africa ; female partners of migrant workers returning to Mozambique for short periods ; and women at high risk of HIV infection in South Africa . Participants in all these studies broadly welcomed the opportunity to avoid HIV infection but were apprehensive about being seen to take ART.…”
Section: Resultsmentioning
confidence: 99%
“…HIV pre-exposure prophylaxis (PrEP) could also be introduced, which could be particularly important for the large portion (39%) of female PWID engaged in transactional/commercial sex[17] but not engaged in existing interventions for female sex workers. Although PrEP is currently recommended as a prevention choice for PWID in Kenya[37], the knowledge of PrEP among female PWID will need improving[38] to ensure PrEP can have impact. Interventions should also consider non-injecting drug users, as newly initiating injectors already have high HIV prevalence, suggesting considerable sexual HIV transmission occurs before initiating injecting drug use.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in a study among individuals attending syringe exchange programs in New Jersey, WWID were more willing to use PrEP than their male counterparts (88.9 vs. 71.0%; p < 0.02) (43). Beyond gender, factors which influenced the acceptability of PrEP included concerns regarding side-effects (25,33,34,43,55), and access to health professionals (22,34,43). Participants who found PrEP more acceptable were those that engaged in sex work (25, 46) or transactional sex (43), had experienced sexual violence (41), had multiple recent sexual partners (25, 43), had other medical conditions (47), shared injection equipment (41, 46, 47), believed they were at high risk of HIV (48), and were of younger age (25, 41).…”
Section: Prep Acceptabilitymentioning
confidence: 99%